2018
DOI: 10.1021/jacs.8b09441
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Allosteric Regulation in Cytochrome P450cam (CYP101A1)

Abstract: Various biophysical methods have provided evidence of a second substrate binding site in the well-studied cytochrome P450cam, although the location and biological relevance of this site has remained elusive. A related question is how substrate and product binding and egress occurs. While many active site access channels have been hypothesized, only one, channel 1, has been experimentally validated. In this study, molecular dynamics simulations reveal an allosteric site related to substrate binding and product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(112 citation statements)
references
References 45 publications
10
99
3
Order By: Relevance
“…Most recently, Chuo et al argued for a closed ➔ open conformational change induced by Pdx binding, and they also found intermediate states. Our current work does support some aspects of the most recent models developed by other groups; to determine whether there are any larger scale conformational changes in addition to what we report herein would involve additional, very extensive computational studies, which are in process in our labs.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Most recently, Chuo et al argued for a closed ➔ open conformational change induced by Pdx binding, and they also found intermediate states. Our current work does support some aspects of the most recent models developed by other groups; to determine whether there are any larger scale conformational changes in addition to what we report herein would involve additional, very extensive computational studies, which are in process in our labs.…”
Section: Introductionsupporting
confidence: 73%
“…Prior studies have shown that Pdx docking to P450cam brings about major structural alterations, and it has been proposed that Pdx is not only needed for the electron transfer, but is also vital to trigger structural changes which are required for the subsequent catalytic activity. Recently, Follmer et al carried out MD simulations supporting a second, allosteric site related to substrate binding and product egress, with some cooperativity indicated between this site and the original substrate binding site . In subsequent work, Follmer et al also provided experimental results which appeared to strengthen their proposed allosteric binding mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…This seemingly simple P450 is also complex due to the issue of multiple ligand occupancy (74 -77). Furthermore, conversion of high-spin iron back to low-spin occurs upon binding of the second molecule of camphor (substrate) (75,77). Relevant to the present work is the multiplicity of X-ray crystal structures of ligand-free P450 cam existing in both closed (78) and open (79) forms.…”
Section: Kinetics Of P450-substrate Bindingmentioning
confidence: 85%
“…Considerable evidence exists for multiple conformations of P450 enzymes. The well-studied bacterial model P450 cam (P450 101A1) has been shown to exist in both open and closed states, and the relevance of these in different steps in the catalytic cycle is a subject of current interest (5)(6)(7)(8)(9). Another bacterial P450, OleP, has been recently reported to show multiple conformations in the presence of a substrate analog (10).…”
mentioning
confidence: 99%